DOP69 Ozanimod for induction treatment of Moderate-to-Severe Ulcerative Colitis: Results from a systematic literature review and network meta-analyses. (27th May 2021) - Eaton, K; Duperrouzel, C; Bhandari, P; Craigie, S; Bonner, A; Cameron, C; Tencer, T; Kumar, J
Abstract: Background: Ozanimod (OZA) is an orally administered, selective sphingosine-1-phosphate receptor modulator that has been evaluated versus placebo (PBO) in the phase 3 True North trial in the treatment of adult patients with moderate-to-severe ulcerative colitis (UC). The objective of this study was to compare the relative efficacy of OZA versus other approved moderate-to-severe UC therapies via network meta-analyses (NMA). Methods: A systematic literature review was conducted to identify randomised clinical trials published from Jan 1, 2000 to Oct 21, 2020 that evaluated biological therapies (infliximab [IFX], adalimumab [ADA], golimumab [GOL], vedolizumab [VEDO], and ustekinumab [UST]) or an oral small molecule (tofacitinib [TOF]) for adults with moderate-to-severe UC. Bayesian NMAs were performed to determine the comparative efficacy of these therapies based on clinical remission, clinical response, and endoscopic improvement in the induction phase (6 to 14 weeks). Three populations were considered: all patients (overall), first-line (biologic-naïve), or those with exposure to or failure of prior biologic therapy (biologic-experienced). All six comparator therapies were included in the overall and biologic-naive populations, whereas the biologic-experienced population included ADA, VEDO, UST, and TOF due to lack of biologic-experienced data for IFX and GOL. Results: Twenty-two RCTs examining 10, 269 patients in the induction phase were included (Figure 1). All therapies offered significant improvement over PBO across networks apart from ADA in the analysis of clinical remission and clinical response in the biologic-experienced population and ADA, VEDO, and OZA in the analysis of endoscopic improvement in the biologic-experienced population. In the overall and biologic-naïve populations, OZA offered similar efficacy to all other therapies across endpoints except for a significant improvement in endoscopic improvement over ADA (overall: OR 2.01, 95% CrI 1.14, 3.66 [Figure 2]; biologic-naïve: OR 2.13, 95% CrI 1.02, 4.50 [Figure 3]). OZA also offered similar efficacy to all other therapies across endpoints in the biologic-experienced population except for an improvement in clinical remission (OR 4.16, 95% CrI 1.55, 11.24) and clinical response (OR 3.11, 95% CrI 1.40, 7.08) over ADA (Figure 4). Conclusion: This NMA suggests that OZA provides similar induction efficacy on clinical remission, clinical response, and endoscopic improvement versus other approved moderate-to-severe UC therapies regardless of prior biologic treatment status.